2020
DOI: 10.1007/s12041-020-01233-7
|View full text |Cite
|
Sign up to set email alerts
|

Age-related gene expression alterations by SARS-CoV-2 infection contribute to poor prognosis in elderly

Abstract: The ongoing pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has affected millions of people worldwide and with notable heterogeneity in its clinical presentation. Probability of contracting this highly contagious infection is similar across age groups but disease severity and fatality among aged patients with or without comorbidities are reportedly higher. Previous studies suggest that age associated transcriptional changes in lung and immune system results in a proinflammatory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Consequently, the study of the intersection between SARS-CoV-2 and ageing-related molecular alterations could augment the understanding of COVID-19, thus improving treatment options [8] . Bhattacharyya et al presented a first analysis based on some preliminary public data reinforcing the rationale that such a possible link exists [5] . The expression of the two human receptors TMPRSS2 and ACE2, which are recognised by the SARS-CoV-2 protein Spike, increases with age in mammals [7] , further suggesting a molecular cause for the more severe COVID-19 symptoms with age.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the study of the intersection between SARS-CoV-2 and ageing-related molecular alterations could augment the understanding of COVID-19, thus improving treatment options [8] . Bhattacharyya et al presented a first analysis based on some preliminary public data reinforcing the rationale that such a possible link exists [5] . The expression of the two human receptors TMPRSS2 and ACE2, which are recognised by the SARS-CoV-2 protein Spike, increases with age in mammals [7] , further suggesting a molecular cause for the more severe COVID-19 symptoms with age.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the study of the intersection between SARS-CoV-2 and ageing-related molecular alterations could augment the understanding of COVID-19, thus improving treatment options [44]. Bhattacharyya et al presented a first analysis based on some preliminary public data reinforcing the rationale that such a possible link exists [45].…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence reports that critically ill patients have elevation in IL-6 levels compared to moderately ill patients [36]; in addition to the in ltration of in ammatory cells, immune cells have been found in patients's lung tissues. Notably, disease-associated transcriptional change in aged whole blood had a more pronounced overlap with control blood in comparison to lung tissue transcriptome [53]. By interacting host genes with SARS-CoV-2 and blood transcriptome, Bhattacharyya and Thelma [53] further suggested that viral infection only alters expression pro le already dysregulated in the elderly, thereby resulting in poor prognosis; these altered blood genes may reinforce the appearance of severe clinical manifestations including strokes, blood clots, and heart failures.…”
Section: Discussionmentioning
confidence: 99%